আলোর মিছিল - সাহা, সত্য (Laser Vision, 2010)
Rana, a young man who fought for the freedom of Bangladesh returns home after getting a treatment for his injured leg , which he got during the freedom struggle. Rana has young niece named Alo, who is studing in college and very close to him. Rana loves Dina, daughter of a rich businessman. Many questions arises in Rana's mind about his brother Alim's business, and how he became rich suddenly after independence of Bangladesh. Rana's brother and Dina's father were involved in black marketing and other illegal ways of business. Rana, his brother's friend Sahid along with others protested against all these corruptions and become enemy of these businessme